Implementation Of Character Through Local Wisdom In Early Childhood - Suharyati, Henny; Wulandari, Dian; N, Lina (UNIVERSITAS PAKUAN, 2024)
This study investigates the potential of wayang beber wisdom to enhance some facets of preschoolers' educational character in Bogor. Character-building exercises in early childhood education in Bogor are required to emphasize the basic virtues of cooperation, courage, bravery, honesty, and responsibility. The educational program makes use of the wayang beber's natural beauty to teach kids this lesson. In-depth interviews with five certified PAUD instructors who are in charge of looking after kids between the ages of 5 and 6 were used in this study. Six key topics about the advantages of incorporating wayang beber stories into learning to boost kids' interest in character development were highlighted by data collected from interviews with instructors who took part in this research. Care for Others, Rewarding Courage, Cooperation, Honor, Responsibility, and Honesty are some of these concepts. The six basic personal character principles are included into classroom education, according to teachers, and this fosters beneficial improvements in students' social interactions and behavior. Children will also be more equipped to proactively deal with issues in daily life when wayang beber stories are integrated with character development.